Seeing it from both sides: do approaches to involving patients in improving their safety risk damaging the trust between patients and healthcare professionals? An interview study. - Susan Hrisos; Richard Thomson (PLoS ONE)
Objective Encouraging patients to be more vigilant about their care challenges the traditional dynamics of patient-healthcare professional interactions. This study aimed to explore, from the perspectives of both patients and frontline healthcare staff, the potential consequences of patient-mediated intervention as a way of pushing safety improvement through the involvement of patients. Design Qualitative study, using purposive sampling and semi-structured interviews with patients, their relatives and healthcare professionals. Emergent themes were identified using grounded theory, with data coded using NVIVO 8. Participants 16 patients, 4 relatives, (mean age (sd) 60 years (15); 12 female, 8 male) and 39 healthcare professionals, (9 pharmacists, 11 doctors, 12 nurses, 7 health care assistants). Setting Participants were sampled from general medical and surgical wards, taking acute and elective admissions, in two hospitals in north east England. Results Positive consequences were identified but some actions encouraged by current patient-mediated approaches elicited feelings of suspicion and mistrust. For example, patients felt speaking up might appear rude or disrespectful, were concerned about upsetting staff and worried that their care might be compromised. Staff, whilst apparently welcoming patient questions, appeared uncertain about patients' motives for questioning and believed that patients who asked many questions and/or who wrote things down were preparing to complain. Behavioural implications were identified that could serve to exacerbate patient safety problems (e.g. staff avoiding contact with inquisitive patients or relatives; patients avoiding contact with unreceptive staff). Conclusions Approaches that aim to push improvement in patient safety through the involvement of patients could engender mistrust and create negative tensions in the patient-provider relationship. A more collaborative approach, that encourages patients and healthcare staff to work together, is needed. Future initiatives should aim to shift the current focus away from "checking up" on individual healthcare professionals to one that engages both parties in the common goal of enhancing safety.